Mys retrotransposons in Peromyscus leucopus and transgenic Mus musculus. - Pine, D S (1988)
The mys family of retrotransposons exhibits an interesting phylogenetic distribution with 500-1000 copies per haploid genome in the white-footed mouse Peromyscus leucopus and no copies detectable in the house mouse Mus musculus, even though most other repeated sequences are shared by these two species. Comparison of the DNA sequences from the 3' ends of five mys elements show that insertion occurs just upstream of a well-conserved 11 bp target sequence. Transcription patterns of the elements in brain, liver, heart, kidneys and gonads in Peromyscus leucopus are analyzed. Transcripts are found in all tissues examined, but they are remarkably heterogeneous in size. When four cloned elements are introduced into transgenic Mus musculus, however, discrete patterns of expression are revealed. Furthermore, a study of the structure of the concatemers of mys elements in the transgenic mice demonstrates that recircularization of injected linear molecules is an important event in concatemer generation.